Enzymatic and antibacterial activity of some actinomycete strains - Jamyanmyadag, Munguntuya; Battsetseg, Choidash; Oyukhan, Khandaa; Sainbileg, Purevjav; Erdenechimeg, Shagdar; Rentsenkhand, Tserennadmid; Pagmadulam, Baldorj (Proceedings of the Institute of Biology, 2022)
The soil samples were collected from the Tuv provinces of Mongolia. Three cultures of actinomycetes were isolated and extracted bioactive crude extract with organic solvents, and their antimicrobial activity and some enzyme activities were determined. Actinomycetes 24-TSAND1, 21-TSB8, and 54-TSB4 had protease and amylase enzyme activities Cultures of actinomycetes 24-TSAND1, 21-TSB 8, and 54-TSB4 are highly active against pathogenic bacteria Staphylococcus aureus. However, 24-TSAND1 and 21-TSB 8 cultures were not effective against Escherichia coli pathogens, while 54-TSAND4 culture was moderately active. Also, the nucleotide sequence of the 16S rRNA gene of the actinomycete 24-TSAND1 culture was determined, and the phylogenetic analysis revealed that it depends on the species of Streptomyces microflavus. Зарим актиномицетийн нутгийн өсгөвөрүүдийн ферментийн болон бичил биетний эсрэг идэвх Төв аймгийн хөрснөөс ялгасан актиномицетийн 3 өсгөврийг сонгон органик уусгагчаар хандлан бичил биетний эсрэг идэвх болон зарим ферментийн идэвхийг тодорхойлов. Актиномицетийн 24-Цанд1, 21-ЦБ8 болон 54-ЦБ4 өсгөврүүд нь протеаза, амилаза ферментийн өндөр идэвхтэй байна. Актиномицетийн 24-Цанд1, 21- ЦБ8, 54-ЦБ4 нутгийн өсгөврүүд өвчин үүсгэгч S. aureus–ийн эсрэг идэвх өндөртэй байна. Харин E. coli өвчин үүсгэгчийн эсрэг 24-Цанд1, 21-ЦБ8 өсгөврүүд үйлчлээгүй бол 54-ЦБ4 өсгөвөр дунд зэргийн идэвхтэй байв. Мөн актиномицетийн 24-Цанд1 өсгөврийн 16S рРНХ генийн нуклеотидийн дарааллыг тогтоож, филогенетикийн анализ хийхэд Streptomyces microflavus-ийн төрөл зүйлд хамаарч байгааг тодорхойлов. Түлхүүр үгс: Актиномицет, 16S рРНХ ген, филогенетик, фермент, бичил биетний эсрэг идэвх